Lower CSF Amyloid Beta Peptides and Higher F2-Isoprostanes in Cognitively Intact Elderly Individuals With Major Depressive Disorder - Pomara, Nunzio; Bruno, Davide; Sarreal, Antero S.; Hernando, Raymundo T.; Nierenberg, Jay; Petkova, Eva; Sidtis, John J.; Wisniewski, Thomas M.; Mehta, Pankaj D.; Pratico, Domenico; Zetterberg, Henrik; Blennow, Kaj (The American journal of psychiatry, 2012)
Objective:Major depressive disorder is common in the elderly, and symptoms are often not responsive to conventional antidepressant treatment, especially in the long term. Soluble oligomeric and aggregated forms of amyloid beta peptides, especially amyloid beta 42, impair neuronal and synaptic function. Amyloid beta 42 is the main component of plaques and is implicated in Alzheimer's disease. Amyloid beta peptides also induce a depressive state in rodents and disrupt major neurotransmitter systems linked to depression. The authors assessed whether major depression was associated with CSF levels of amyloid beta, tau protein, and F2-isoprostanes in elderly individuals with major depressive disorder and age-matched nondepressed comparison subjects. Method:CSF was obtained from 47 cognitively intact volunteers (major depression group, N=28; comparison group, N=19) and analyzed for levels of soluble amyloid beta, total and phosphorylated tau proteins, and isoprostanes. Results:Amyloid beta 42 levels were significantly lower in the major depression group relative to the comparison group, and amyloid beta 40 levels were lower but only approaching statistical significance. In contrast, isoprostane levels were higher in the major depression group. No differences were observed in total and phosphorylated tau proteins across conditions. Antidepressant use was not associated with differences in amyloid beta 42 levels. Conclusions:Reduction in CSF levels of amyloid beta 42 may be related to increased brain amyloid beta plaques or decreased soluble amyloid beta production in elderly individuals with major depression relative to nondepressed comparison subjects. These results may have implications for our understanding of the pathophysiology of major depression and for the development of treatment strategies.